Virtual consultations for oral surgery patients - Aoife Crummey; Abigail Graham; Eleni Besi (BMC, 2022)
Abstract Background Following Covid-19, many departments have incorporated teledentistry into practice. As new consultation methods are introduced, it's imperative that patients have as similar an experience with virtual consultations to ensure informed decision-making. This project evaluated patients' perceptions of video consultations and determined if patients seen virtually received the same standard of information by auditing compliance with sending patient information leaflets (PILs) following video consultation. Method The department's PILs were used to create an inclusion list for patients requiring a PIL. A retrospective audit assessed the notes of 100 video consultations for records of if PILs were sent and by what method. The department's PILs were digitalised and a clinical mailbox introduced enabling clinicians to email patients a PIL hyperlink. The audit was repeated for 88 video consultations. Patient and staff feedback was gathered via online surveys. Results Initially, 51% of cases met the criteria requiring a PIL and 16% of patients were sent PILs. Following mailbox introduction, 53% of cases met the criteria and 94% were sent PILs, 100% via email. Patient and staff feedback was positive regarding video consultations and digital PILS. Technical difficulties were reported in 44% of cases. Conclusions Patients perceive virtual consultations to be a positive change and the introduction of a mailbox enhances video consultations in an efficient and cost-effective manner. Patient information can be standardised, via digital PILs, regardless of consultation type. As departments implement post-pandemic changes, utilisation of a mailbox can provide multiple improvements to care.